Roles of Insect Oenocytes in Physiology and Their Relevance to Human Metabolic Diseases - Huang, Kerui; Liu, Ying; Perrimon, Norbert (Frontiers in Insect Science, 2022)
Oenocytes are large secretory cells present in the abdomen of insects known to synthesize very-long-chain fatty acids to produce hydrocarbons and pheromones that mediate courtship behavior in adult flies. In recent years, oenocytes have been implicated in the regulation of energy metabolism. These hepatocyte-like cells accumulate lipid droplets under starvation and can non-autonomously regulate tracheal waterproofing and adipocyte lipid composition. Here, we summarize evidence, mostly from Drosophila, establishing that oenocytes perform liver-like functions. We also compare the functional differences in oenocytes and the fat body, another lipid storage tissue which also performs liver-like functions. Lastly, we examine signaling pathways that regulate oenocyte metabolism derived from other metabolic tissues, as well as oenocyte-derived signals that regulate energy homeostasis.